ANALYSIS OF LEARNING WEB APPLICATION TESTING WITH WEIGHTING PRODUCT AND ORDERED WEIGHTING AVERAGING ON GROUP DECISION MAKER - St. Hatijah H. Ilyas; St. Hajrah Mansyur; Harlinda (Jurnal Teknik Informatika (Jutif), 2022)
In 2019-2021, almost every country in the world is being hit by an outbreak of Corona Virus Disease (Covid-19) which has a major impact on various fields, one of which is in the field of education. Utilizing learning web applications is one way to carry out teaching and learning activities so that students continue to learn. Web application testing is the process of running software to find errors in the content, interface, navigation, components, configuration, performance and security of web applications. The purpose of this study is to analyze the testing of the learning web application of the Rumah Belajar Kemdikbud, Kelas Pintar, and Sekolahmu based on seven criteria aspects. The method used is the Weighting Product (WP) method to determine the results of web application testing based on seven aspects and to integrate web application testing assessments from the Group Decision Maker using the Ordered Weighting Averaging (OWA) method. The results showed the level of accuracy after testing the Web-Test application and manual calculations in Microsoft Excel using the WP method was 90% while the OWA method was 80%.